2021
DOI: 10.3390/su13084140
|View full text |Cite
|
Sign up to set email alerts
|

50 Shades of Green: Insights into Personal Values and Worldviews as Drivers of Green Purchasing Intention, Behaviour, and Experience

Abstract: Despite the booming interest in determinants of green (i.e., sustainable) consumption, the psychological factors that influence pro-environmental consumption patterns are not yet fully understood. To answer this call, we developed and analysed a model that offers an integrative approach to sustainable consumption patterns by addressing the full palette of consumers’ personal value orientations. Specifically, we linked consumers’ egoistic, altruistic, and biospheric values at the personal level to pro-environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 68 publications
(136 reference statements)
0
8
1
Order By: Relevance
“…De Groot and Steg (2007) found, in a study on personal value orientations in five European countries in environmental behaviour perspective, that altruistic value orientation of Swedish respondents, unlike in four other countries, was very strongly related to both personal norms and awareness of consequences. In another study, in contrast to biospheric value orientation, altruistic value orientation was not at all related to pro-environmental behaviour in Poland (Caniels et al, 2021) Regarding some sociodemographic variables, such as age and education, our study differs from many previous studies. For example, in Canada (N = 1251), adults showed significantly higher levels of emotional connectedness to nature compared to adolescents (Anderson & Krettenauer, 2021).…”
Section: Cross-country Differences In Hnccontrasting
confidence: 99%
See 1 more Smart Citation
“…De Groot and Steg (2007) found, in a study on personal value orientations in five European countries in environmental behaviour perspective, that altruistic value orientation of Swedish respondents, unlike in four other countries, was very strongly related to both personal norms and awareness of consequences. In another study, in contrast to biospheric value orientation, altruistic value orientation was not at all related to pro-environmental behaviour in Poland (Caniels et al, 2021) Regarding some sociodemographic variables, such as age and education, our study differs from many previous studies. For example, in Canada (N = 1251), adults showed significantly higher levels of emotional connectedness to nature compared to adolescents (Anderson & Krettenauer, 2021).…”
Section: Cross-country Differences In Hnccontrasting
confidence: 99%
“…De Groot and Steg (2007) found, in a study on personal value orientations in five European countries in environmental behaviour perspective, that altruistic value orientation of Swedish respondents, unlike in four other countries, was very strongly related to both personal norms and awareness of consequences. In another study, in contrast to biospheric value orientation, altruistic value orientation was not at all related to pro‐environmental behaviour in Poland (Caniels et al, 2021). Even if the above findings do not explain the weak association between altruistic orientation and HNC in Sweden and Poland in our study, they clearly illustrate the differences between countries.…”
Section: Discussionmentioning
confidence: 91%
“…The focus in this paper is on whether teaching can influence the awareness of fragility issues as well as low probability, high impact events, by means of an experiment in a marketing course for management students of a large private business school in Wrocław (Poland) in April-May 2019. Business students have been described in the literature as being strongly focused on economic gain and bottom line thinking, yet recent studies added nuance to the debate, describing different segments when it comes to perceptions regarding sustainability (Lambrechts et al 2018b) and pro-environmental behavior (Caniëls et al 2021).…”
Section: Introduction -The Importance Of Teaching Interventions In Ed...mentioning
confidence: 99%
“…"The people I'm going to meet tonight, they are all vegetarians you know, so they are in a way living a sustainable life … I would rather be around people that are eating in that way, rather than people who are eating in a non-sustainable way." (Male,46) Research has highlighted the importance of friendships when behaving sustainably, especially among young people (Caniëls et al, 2021). Participants in our study indicated that their engagement with sustainable living was both reinforced by friends living similarly, and simultaneously driven by a desire to deepen bonds with such friends.…”
Section: "I Think Probably I Am More Like This [Engaging In Sustainab...mentioning
confidence: 65%